The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1063/1.3499272
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical characterization of pulse-modulated argon atmospheric-pressure inductively coupled microplasma jets

Abstract: The critical parameters determining the generation of the pulse-modulated argon atmospheric-pressure inductively coupled plasma (AP-ICP) microjet were studied by varying the power, P, pulse-modulation frequency, f, and duty ratio, DR. The temporal changes in the net output power, Pnet, monitored between the very high frequency power supply and matching network by an rf sampler, and ArI 4s′[1/2]1O–4p′[1/2]0 emission from the antenna were measured to elucidate the behavior of this plasma. The AP-ICP microjet, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…By downsizing the plasma reactor, the surface to volume ratio increases making the ICP mode still more efficient. There are many variants of inductive coupling to a plasma [7][8][9][10][11][12][13][14][15][16]. To our knowledge none of these papers makes an analysis of the E-H mode transition and of the efficiency of the power transferred to the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…By downsizing the plasma reactor, the surface to volume ratio increases making the ICP mode still more efficient. There are many variants of inductive coupling to a plasma [7][8][9][10][11][12][13][14][15][16]. To our knowledge none of these papers makes an analysis of the E-H mode transition and of the efficiency of the power transferred to the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric pressure glow discharges (APGDs) [1][2][3][4] have attracted great interest because of their enormous advantages such as no expensive vacuum systems, the absence of heat damage due to the operation in the nonthermal glow and the capability to produce reactive species, charged particles, and UV radiation. In recent years, various types of APGDs have been developed to apply in material processing [5], biomedical processing [6,7], nanotechnology [8], conventional etching [9], and deposition [10].…”
Section: Introductionmentioning
confidence: 99%
“…The external power supply (for example, a high voltage DC or AC power supply) for generating a thermal electron or dielectric barrier discharge is used. [19][20][21][22] Ito et al reported regarding using tungsten wire, which is usually connected to ground; for generating thermal electrons, a pulse of about a 15 kV voltage is applied to 0.5 s. 23) This means there is a necessity for a supply of additional power and additional wiring. The miniaturization of the plasma source is disturbed, making the total system complicated with the additional power source.…”
Section: Introductionmentioning
confidence: 99%